Simulation Experiment of Constraint Force in the Spatial RCCR Mechanism with three pairs of Force Transmitting Rods - Zhuang Sen; Han Bo; Liu Zhongyi; Huang Xiaolei; Cui Chao (Jixie chuandong)
Using bushings with great stiffness coefficient to replace the rigid constraints,the dynamics simulation of the over-constrained spatial RCCR mechanism with three pairs of force transmitting rods under conditions approaching rigidity is achieved.The simulation experiment targeting different structural parameters and resistance moment,the variation discipline of transmitted force is obtained,the cosine function type of constraint component Fz is fitted out,the estimation formula of Fz amplitude is summed.